2006
DOI: 10.1258/095646206778113078
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnoea among HIV patients

Abstract: The development of body weight gain and lipodystrophy due to antiretroviral therapy may lead to disturbances in sleep, particularly the obstructive sleep apnoea (OSA) syndrome. A retrospective review of the medical records of consecutively identified HIV-infected subjects who were diagnosed with OSA by overnight polysomnography between January 1, 2003 and December 31, 2004 was performed. Twelve HIV-infected subjects with OSA confirmed by polysomnography (total apnoea/hypopnoea index > or = 5) were identified. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 0 publications
0
22
1
Order By: Relevance
“…Furthermore, obstructive sleep apnea has been reported in patients with acquired lipodystrophy syndromes, specifically partial lipodystrophy associated with HIV infection treated with highly active antiretroviral drugs. 7 No clear mechanism links familial partial lipodystrophy subtype 2 with obstructive sleep apnea, although both of the patients we have described were of normal weight but had markedly increased neck fat content, specifically in the region surrounding the trachea. This suggests that the association might be related to the repartitioning of adipose tissue that is characteristic of patients with this type of lipodystrophy.…”
mentioning
confidence: 78%
“…Furthermore, obstructive sleep apnea has been reported in patients with acquired lipodystrophy syndromes, specifically partial lipodystrophy associated with HIV infection treated with highly active antiretroviral drugs. 7 No clear mechanism links familial partial lipodystrophy subtype 2 with obstructive sleep apnea, although both of the patients we have described were of normal weight but had markedly increased neck fat content, specifically in the region surrounding the trachea. This suggests that the association might be related to the repartitioning of adipose tissue that is characteristic of patients with this type of lipodystrophy.…”
mentioning
confidence: 78%
“…Compliance to HAART favors fat redistribution in PLWHA: visceral as well as lipodystrophy (Lo Re et al 2006;Kosmiski et al 2003). Brigham and collaborators (McNicholas 2009) demonstrated that PLWHA not on HAART with moderate to severe OSA have high circulating levels of inflammatory markers especially TNF-alpha, compared to those with no-to-mild OSA after adjustment for age, race, smoking status, obstructive lung disease and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…OSA is usually associated with obesity (Gupta et al 2010;Resta et al 2001) and the onset of sleep apnea frequently follows a marked increase in body weight (Smith et al 1988). However, obesity alone is not essential for the development of OSA (Resta et al 2001;Lo et al 1998;Joy et al 2008;Lo Re et al 2006;Dorey-Stein et al 2008;Epstein et al 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…
Aims Obstructive sleep apnoea (OSA) has been described in 2 small studies of adults with human immunodeficiency virus (HIV) and appears to be associated with higher body mass index1 and adenotonsillar hypertrophy 2. However, there are few data in children and the possibility of an association with cerebrovascular disease has not been addressed.
…”
mentioning
confidence: 99%